Plasma C1q/tumor necrosis factor-related protein-3 concentrations are associated with diabetic peripheral neuropathy. Issue 2 (5th April 2022) - Lin, Ke; Yang, Liu; Xiong, Yuyuan; Feng, Keduo; Zeng, Wang; Deng, Bo
Abstract : Introduction: To analyze the associations of circulating C1q/tumor necrosis factor-related protein-3 (CTRP3) concentrations with several metabolic parameters and to investigate the possible role of CTRP3 in subjects with diabetic peripheral neuropathy (DPN). Research design and methods: A total of 347 participants were recruited in this study, and plasma CTRP3 concentrations were analyzed in subjects with DPN (n=172) and without DPN (non-DPN, n=175). The nerve conduction test and oral glucose tolerance test were performed, and Neuropathy Symptom Score (NSS)/Neuropathy Disability Score (NDS) and biochemical parameters were measured in all participants. Results: Plasma CTRP3 concentrations were significantly lower in patients with DPN compared with those in patients with diabetes without DPN (p<0.01), despite the comparable glucose and lipid metabolism levels in both groups. Groups with a higher plasma CTRP3 level had a faster nerve conduction velocity. In addition, plasma CTRP3 concentrations were negatively correlated with hemoglobin A1c (HbA1c), urea acid (UA), triglyceride, NSS and NDS (p<0.05) after being adjusted for age and sex. Multivariate logistic regression analysis revealed that plasma CTRP3 concentrations were significantly correlated with DPN after being controlled for age, sex, body mass index, HbA1c, blood pressure, lipid profiles, and renal function. Conclusions: Plasma CTRP3 concentrations were significantly lower in patients with DPM and positively correlated with nerve conduction velocity. The relationship between CTRP3 levels and DPN is independent of the glucose and lipid status. Therefore, circulating CTRP3 might serve as a predictor of impairment of nerve conduction in patients with DPN.